2011
DOI: 10.4103/0972-6748.102475
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive reserve: The warehouse within

Abstract: Dementia is characterized by progressive and mostly irreversible memory loss. Other neuropsychiatric disorders affect cognition in varying manner. Are all people affected with such disorders manifest clinically in similar manner or does our brain have some reserve to tolerate insults? Relevant researches over the last two decades were scrutinized to understand brain reserve, appreciate the conceptual change in the same over years, and how the same can be improved for better cognition and memory over the year. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…In the current study, low level of education was significantly associated with the degree of cognitive impairment. This finding is also supported by Prakash et al [44] who demonstrated that the higher the educational level, the lesser the risk of cognitive impairment. Similarly, Yerrapragada et al [1] showed that low level of education is associated with lower cognitive scores.…”
Section: Discussionsupporting
confidence: 70%
“…In the current study, low level of education was significantly associated with the degree of cognitive impairment. This finding is also supported by Prakash et al [44] who demonstrated that the higher the educational level, the lesser the risk of cognitive impairment. Similarly, Yerrapragada et al [1] showed that low level of education is associated with lower cognitive scores.…”
Section: Discussionsupporting
confidence: 70%
“…On this note, if the preclinical stage of AD consists of a reduction of semantic encoding abilities, then it is unsurprising that low levels of education are one of the crucial risk factors for developing the disease. This may shed new light on the role of education levels as integral part of the concept of cognitive reserve, a well-established protecting factor for the onset of AD symptoms [45].…”
Section: Discussionmentioning
confidence: 98%
“…Evidence for this association conflicts. Prakash et al 35 and Brayne and Calloway 36 showed that higher educational attainment is associated with reduced chance of cognitive impairment. On the other hand, studies by Andel et al 37 and Stern et al 38 showed that education attainment was associated with accelerated cognitive decline in patients with Alzheimer disease.…”
Section: Discussionmentioning
confidence: 99%